Usborne Phonics Readers : Bug in a Rug - Russell Punter (London, United Kingdom Usborne Publishing Ltd, 2015)
A funny picture book featuring a madcap story about a bug who just wants to get snug in his rug, which uses phonic repetition to help children learn to read. The simple rhyming text helps to develop essential language and early reading skills, and there are guidance notes for parents at the back of the book.
Keywords: PY - Language